Economic multisectoral modelling between past and future A tribute to Maurizio Grassini and a selection of his writings - Bardazzi, Rossella (Studi e saggi, 2013)
This book is a tribute to the work of Maurizio Grassini, econometrician and model builder. The selection of his works in the first part of the volume is mainly devoted to research issues of multisectoral modelling. In fact, M. Grassini has dedicated a large part of his professional life to building and developing the INTIMO model for the Italian economy within the INFORUM research project. The book does not aim to be a celebration of the past but takes a look at the future of the multisectoral modelling which M. Grassini has contributed so much to. In the second part of the book, colleagues and friends who have encountered M. Grassini in the professional sphere on matters of quantitative economic analysis or still working with him on interindustry models have given their contribution to look at the future prospects of a research field firmly based on the experience of what has been done so far.